Characterisation of Non-Dermatophyte Fungus on The Toes of a Patient Diagnosed with Tinea Pedis - Yolan Dunggio; Ismail Mukusibu (Universitas Nahdlatul Ulama Surabaya, 2023)
In a health center-level morbidity data report by the Gorontalo City Health Office in 2020, the prevalence of fungal-related skin diseases attained 4.76 percent (476 cases), including 56 cases of tinea pedis. One of the variables in athlete's foot is a workplace and type(s) of work that fail to satisfy basic health guidelines. In the case examined by this study, the patient was a butcher employed locally in a small shop. This study aims to use a variety of parameters to describe the non-dermatophyte fungi that cause butcher's toe infections. Fungus characteristics were performed macroscopically and microscopically. The observations were used to describe the characteristics of the fungus, which were then analysed descriptively with reference to the identification manuals book. Non-dermatophyte fungi such as Aspergillus sp., Rhizopus sp., Candida albicans, were identified in the study findings. Aspergillus sp., Rhizopus sp., Candida albicans and other types of fungi such as Metarhizium anisopliaea. This study demonstrates that non-dermatophyta fungal infections may be the source of butchers' tinea pedis.